Poverty and Environment : Understanding Linkages at the Household Level - World Bank (Washington, DC: World Bank, 2012)
This report seeks to present micro evidence on how environmental changes affect poor households. It focuses primarily on environmental resources that are outside the private sphere, particularly commonly held and managed resources such as forests, fisheries, and wildlife. The objectives for this volume are three-fold. It is first interested in using an empirical data-driven approach to examine the dependence of the poor on natural resources. The second objective is to examine the role of the environment in determining health outcomes. A third area of interest concerns the role of policy instruments and reforms. This report uses general economics literature as well as data collected by the World Bank and its partners to analyze poverty-environment linkages at the household level. Poverty-environment linkages are inherently dynamic and involve behavioral responses that make the identification of cause and effect difficult. Thus, questions related to these linkages are ideally answered with the use of panel datasets or with data from randomized experiments.